A journey to a new stable state—further development of the postoperative recovery concept from day surgical perspective: a qualitative study - Maria Jaensson; Karuna Dahlberg; Ulrica Nilsson; Karin Hugelius; Erebouni Arakelian (BMJ Open)
Objective This study aims to further develop the concept analysis by Allvin et al in 2007 and Lundmark et al in 2016 from the perspective of day-surgery patients. Also, to describe how patients experience postoperative recovery in relation to the identified dimensions and subdimensions and to interpret the findings in order to get a deeper understanding of the concept postoperative recovery.Design Descriptive qualitative design with a theoretical thematic analysis.Setting Six day-surgery departments in Sweden.Participants Thirty-eight adult participants who had undergone day surgery in Sweden. Participants were purposively selected.Results Four dimensions—physical, psychological, social and habitual—were confirmed. A total of eight subdimensions were also confirmed, two from Allvin et al’s study and six from Lundmark et al’s study. Recovery included physical symptoms and challenges coping with and regaining control over symptoms and bodily functions. Both positive and negative emotions were present, and strategies on how to handle emotions and achieve well-being were established. Patients became dependent on others. They coped with and adapted to the recovery process and gradually stabilised, reaching a new stable state.Conclusion Postoperative recovery was described as a process with a clear starting point, and as a dynamic and individual process leading to an experience of a new stable state. The recovery process included physical symptoms, emotions and social and habitual consequences that challenges them. To follow-up and measure all four dimensions of postoperative recovery in order to support and understand the process of postoperative recovery is, therefore, recommended.